Hubungan Stres Kerja Perawat Terhadap Burnout Syndrome Pada Perawat Pelaksana Di Ruang Rawat Intensif - Annisa Ulfah; Dian Pitaloka Priasmoro (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2026)
Burnout syndrome is often found in human service professions such as medical and non-medical health workers. In work environments with high levels of complexity such as intensive care units, workload and job stress are triggering factors that greatly influence the occurrence of burnout syndrome. This study aims to determine the relationship between nurses' work stress and burnout syndrome in nurses in the intensive care unit of Ulin Banjarmasin Regional Hospital. The research design used in this study is quantitative with a cross-sectional approach. The study used the Spearman's rank correlation test. The research instruments used were the ENSS (Expanded Nursing Stress Scale) questionnaire to measure work stress and the MBI (Maslach Burnout Inventory) questionnaire to assess the level of nurses' burnout syndrome. The study was conducted in the intensive care unit (ICU/ICCU/PICU) of Ulin Banjarmasin Regional Hospital for one month. Total sampling was used, involving 85 nurses. The results of this study indicate a significant relationship between work stress and burnout syndrome in nurses in the intensive care unit of Ulin Regional Hospital, Banjarmasin, with a p-value of 0.000 (p < 0.05). This finding demonstrates the importance of work stress management and psychological support for nurses to maintain mental health and the quality of nursing services. Nursing professionals, especially those in critical care settings, are expected to better understand the importance of stress management. This will minimize the risk of burnout syndrome and minimize the impact on the quality of care provided to patients.